Sales Promotion Tactics in Retailing: Fair vs Unfair - Wang, Mingrun; Shaari, Nazlina (International Journal of Psychosocial Rehabilitation, 2020)
Chinese parents have been increasingly concerned about the quality of their children’s product. Due to the popularity of parent-child travel, the demand of children's luggage is also increasing, and parents have higher requirements and expectations for children’s luggage. User experience (UX) evaluation can ensure high- quality UX of children’s luggage. However, the methods for evaluating UX in the product development process are still inadequate. Therefore, there is a need to originate a method to evaluate UX of children’s luggage in order to enhance the quality of children’s luggage. An Experience Map was created to evaluate the UX of children’s luggage. Using the map, a total of 12 UXs of children’s luggage was identified. Then, a survey was conducted to evaluate the 12 UXs of children’s luggage. Finally, a strategic decision was made to enhance the quality of children’s luggage. The main contribution of this study was to provide a user experience evaluation method (UXEM) for children’s luggage.